2005
DOI: 10.1136/aim.23.2.70
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Acupuncture for Depression – a Systematic Review of Randomised Controlled Trials

Abstract: Objective To summarise the existing evidence on acupuncture as a therapy for depression. Methods RCTs were included, in which either manual acupuncture or electroacupuncture was compared with any control procedure in subjects with depression. Data were extracted independently by two authors. The methodological quality was assessed. Pre and post means and SDs for depression specific measures were extracted, when available, for meta-analysis. Results Seven randomised comparative trials involving 509 patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 31 publications
0
45
1
1
Order By: Relevance
“…There was also an increasing demand for acupuncture in this field among Western countries as well. In recent years, four systematic reviews, [10][11][12][13] including one Cochrane systematic review, 11 have tried to evaluate the effectiveness and safety of acupuncture for depression, but none of the authors could give a positive and convincing conclusion to support its efficacy and clinical application, because of insufficient high-quality randomized controlled trials. Our previous result of evidence-based medicine research also indicated that, although acupuncture was a very promising modality for depression, there was still insufficient evidence to determine the efficacy of acupuncture because of lack of well-designed studies.…”
Section: Introductionmentioning
confidence: 98%
“…There was also an increasing demand for acupuncture in this field among Western countries as well. In recent years, four systematic reviews, [10][11][12][13] including one Cochrane systematic review, 11 have tried to evaluate the effectiveness and safety of acupuncture for depression, but none of the authors could give a positive and convincing conclusion to support its efficacy and clinical application, because of insufficient high-quality randomized controlled trials. Our previous result of evidence-based medicine research also indicated that, although acupuncture was a very promising modality for depression, there was still insufficient evidence to determine the efficacy of acupuncture because of lack of well-designed studies.…”
Section: Introductionmentioning
confidence: 98%
“…Three (3) recent systematic reviews [56][57][58] indicate that there is insufficient evidence to determine acupuncture's efficacy in the treatment of depression, and recommend the need for further studies. In major depression, compared to invasive acupuncture-like controls at valid acupuncture points, [59][60][61] the effect varies between studies; for depression during pregnancy, 62 acupuncture was significantly more effective than sham.…”
Section: Acupuncture In Mental Health (Schnyer)mentioning
confidence: 99%
“…92 Although these data formed a basis for further investigation, the evidence base from systematic reviews in the mid-2000s suggested that there was insufficient evidence to draw conclusions. 93,94 The evidence for pharmacological antidepressant treatment also raised some concern at the time, with pharmacological antidepressant treatment being associated with up to 33% of patients not showing an adequate response. 95 Moreover, 30% of patients have been found to not adhere to their medication regime.…”
Section: Fundingmentioning
confidence: 99%